Comparison of the Effectiveness of Acceptance and Commitment Therapy and Spiritual Therapy on the Death Anxiety of Women with Breast Cancer - Zamanian, Sakineh; Danesh, Esmat; Bolhari, Jafar; Ahadi, Hasan; Ghahari, Shahrbanoo (Social Determinants of Health, 2019)
Background: Death anxiety is among disruptive factors in mental health of a patient with breast cancer. Therefore, the present study was conducted to compare effectiveness of acceptance and commitment therapy and spiritual therapy on death anxiety of women with breast cancer. Methods: In this quasi-experimental study, 24 women with breast cancer referred to Haft-e-Tir Hospital, Tehran, Iran were included by available sampling method. The participants were randomly assigned to two groups experimental and one control group. They were asked to fill out the Templer Death Anxiety Questionnaire consisting of 15 questions in a 3-month period in 3 phases of pre-test, post-test, and follow-up. Experimental groups received acceptance and commitment therapy and spirituality therapy in eight, 90-minute sessions, and they were followed up 2 months after the interventions. Data analysis was performed using Repeated-Measures ANOVA by SPSS Ver. 21.0. Results: Results of the study showed that, 16 of the participants (66.7%) were 30-50 years old, and 17 of the participants (70.8%) were married. In addition, 15 of the participants (62.5%) had a degree below high school diploma and 15 (62.5%) of the participants had been diagnosed with Breast Cancer for less than one year. Results of the study showed a significant difference in the effect of spiritual therapy on death anxiety compared to acceptance and commitment therapy (P 0.05, F=4.07). On the other hand, the effect of spiritual therapy on death anxiety (P 0.001, F=10.09) was significant. But, acceptance and commitment therapy did not have a significant effect on death anxiety (P 0/05, F=2.704). Conclusion: Since, spiritual involvement and beliefs could account for any of the variation in death anxiety, spiritual therapy was found to improve death anxiety indices in the patients with breast cancer and therefore, the therapists could use this method to improve death anxiety in these patients.